Sistem Perekrutan Karyawan di PT. ABC - Rita Rita; Nurul Mardiah Sitio; Tofa Waluyo Alifya (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Employee recruitment is an important aspect of human resource management that significantly influences the achievement of company goals. The recruitment process is not only about finding the right person for a particular position, but also a long-term strategy to improve the company's competitiveness. Recruitment is a crucial process because it determines the quality of employees who will contribute directly to organizational success. Therefore, companies must ensure that all stages of recruitment run smoothly, are well-directed, and align with the company's real needs. This study uses a descriptive research method with the aim of describing in detail how the recruitment process is carried out at PT. ABC. The research subjects consisted of two key informants, namely the Director and the Personnel Manager. To obtain valid and in-depth data, this study used data collection techniques in the form of direct interviews and field observations. The collected data were then analyzed using a qualitative analysis approach. Qualitative analysis helps to provide a deeper understanding of recruitment practices and their impact on organizational performance. The results of the study indicate that the recruitment process at PT. ABC begins with a thorough planning stage. The company first determines applicant qualifications, prepares clear job specifications, and aligns human resource needs with the company's targets and objectives. This aims to ensure that the recruited workforce truly matches the required competencies. Furthermore, evaluations are conducted periodically to ensure the effectiveness of the recruitment process. The findings highlight that effective recruitment directly influences the company's ability to achieve its long-term objectives. The conclusion of this study is that the recruitment process has a significant impact on company success. With the right recruitment, companies can create competent, loyal human resources who contribute optimally to achieving the organization's vision and mission.